Incidencia de la Inclusión Financiera en la Pobreza del Cantón Guamote de la parroquia La Matriz, periodo 2022. - Chafla Caiza, Nelson Alex (2023)
The purpose of this investigation was to determine the incidence of financial inclusion in the level of poverty of the La Matriz parish of the Guamote canton during the year 2022. For this, the quantitative approach and type of descriptive and correlational research was used with the purpose of describing and relate the dimensions of financial inclusion and the socioeconomic characteristics of Guamoteños with poverty. The process consisted of using a Logit probabilistic model, made up of 374 observations, which led to corroborate that, given an increase in households with access to a financial service point, the possibility that the individual is not poor increases by 0.315 points. percentage points, and the more frequent the use of financial services, the poverty is reduced by 0.386 percentage points. However, the possibility of a household being financially included and reducing its poverty level also depends on the following socioeconomic factors: having an economic activity from which it earns more income, living in an urban area, being older, and owning a high educational level. The investigation is divided into four chapters: Chapter I contains the introduction, problem statement and objectives; Chapter II shows the theoretical framework, with the state of the art and the theoretical foundation of financial inclusion and poverty; Chapter III refers to the methodology, which details: the approach, type, design, techniques, population and sample, and the econometric model; in Chapter IV, the results and discussion are presented, based on the findings derived from the surveys and the estimation of the Logit econometric model; finally, chapter V explains the conclusions and recommendations.